Application of DNA Barcoding in the Classification of Grasshoppers (Orthoptera: Acridoidea)—A Case Study of grasshoppers from Hebei Province, China - Chen, Li-Ping; Chang, Ya-Ge; Li, Jian; Wang, Jian-Mei; Liu, Jin-Lin; Zhi, Yong-Chao; Li, Xin-Jiang (Zootaxa, 2018)
Grasshoppers (Orthoptera: Acridoidea) are the main pests in agriculture, animal husbandry and forestry, and some species of grasshoppers can cause serious disaster. Taxonomy is the basis of pest control. Traditional morphological identification is time-consuming and laborious. It may be due to the existence of cryptic species or the limited number of morphologists, making the identification extremely unstable. In recent years, with the development of molecular systematics, DNA barcoding technology has been applied to environment, ecology, quarantine and so on. This study focuses on testing the feasibility of DNA barcoding in the species identification for superfamily Acridoidea. Sequences of the cox1 gene were obtained from 245 individuals of 43 species of Acridoidea and one species of Tetrigoidea as outgroup from Hebei Province. Phylogenetic, genetic distance and sequence difference threshold analyses using the Maximum Likelihood (ML), Automatic Barcode Gap Discovery (ABGD) and Molecular Defined Operational Taxonomic Units (MOTU) methods, respectively, were performed for obtained sequences and the 139 additional sequences of 21 species downloaded from GenBank. The results have shown that 40, 33, and 35 species among the 48 species are consistent with the traditional morphological classification based on the phylogenetic tree, ABGD and MOTU results, respectively and the DNA barcoding technology is very efficient and helpful for identifying the species of the superfamily Acridoidea; however, the morphological approach is still playing a key role in the species identifications. It also indicates that the cox1 gene is suitable for the phylogeny of genera and species level, but it is not suitable for the phylogenetic relationship of the advanced taxa such as families.